Effect of dietary bile extracts on serum response of astaxanthin in rainbow trout (Oncorhynchus mykiss): a preliminary study - Mendes-Pinto, M.M. (2011)
Effects of porcine bile extracts added at three different dietary concentrations 0, 10 and 20 g kg)1 were studied on astaxanthin serum concentration in rainbow trout (mean weight 200 ± 7 g). Astaxanthin from micro-algae Haematococcus pluvialis and synthetic astaxanthin (CAROPHYLL pink) were incorporated in diets of rainbow trout at a rate of 100 mg astaxanthin kg)1 of feed. Fish were hand fed twice a day. After 5 days of feeding there was a significant effect of the pigment source on the ratio (total blood astaxanthin per unit body weight to cumulative astaxanthin intake per unit body weight). Trout receiving synthetic astaxanthin showed a significantly (P < 0.05) higher ratio than trout fed algal astaxanthin. Increasing dietary bile extract did not lead to produce any effect on this ratio. The power of the statistical analysis is discussed. Therefore, the interaction (pigment source · dietary bile concentration) showed no more effect.